Effect of organic and mineral fertilizers on floored rice yield and chemical and physical properties of Pelotas soil - Machado, Mauri Onofre; Gomes, Algenor da Silva; Turatti, Ariovaldo Luiz; Pauletto, Eloy Antonio; Junior, Paulo Silveira (Pesquisa Agropecuaria Brasileira, 2014)
The effects of seven organic manures and one mineral fertilizer (NPK) were evaluated in this experiment, that was carried out during the rice growing season of 1980/81 and 1981/82, at UEPAE Pelotas Station. In 1980/81 the grain yield was not influenced significantly by any treatments but, in 1981/82, the tanning residue with NPK was the best treatment, followed by coal ash with NPK, rice straw with "nutri-humus" and rice hull with NPK. The mineral fertilizer, farmyard manure, 'humutrim SM-10" and "nitrohumomineral" did not increase significantly the grain yield related to the control. Only the tanning residue with or not NPK caused a sensible modification on the chemical soil properties by increasing the pH, the levels of Ca+2 + Mg+2 and available P and by eliminating the AI+3. The levels of available K in the soil were not influenced by any treatments. The physical soil properties such as particle and bulk density, macro and microporosity, and hydraulic conductivity were not affected by any treatment studied.
Keywords: organic manure; grain yield; tanning residue; chemical soil properties; coal ash; rice hull